Bladder care and management of prolonged/obstructed labor for obstetric fistula: A global survey of intrapartum and postpartum clinical practices - Tripathi, Vandana; Arnoff, Ally (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To understand intrapartum and postpartum clinical practices among skilled birth attendants in low- and middle-income countries (LMICs). Methods: This survey, based on clinical guidelines and curricula, was administered online in French and English, from May-Oct, 2017. Summaries of respondent characteristics, knowledge, and practices were generated. Chi-square tests investigated significant disparities by region, facility type, and geography. Data were analyzed using Stata v12. Results: Respondents (222) were primarily midwives (61%) and OB-GYNs (15%); 56% in Africa and 39% in South-East Asia. A majority practice many recommended practices related to intrapartum/postpartum bladder care and P/OL management. Most reported using partograph to monitor labor (99%), monitoring voiding frequency for postpartum patients (95%), and utilizing UC after P/OL (94%). Findings revealed a lack ofprotocols on bladder care and P/OL management, variation in practice by region, and less access to in-service training and supplies in Africa and public facilities. Conclusions: Findings reveal a strong foundation for standardization in intrapartum/postpartum bladder care and P/OL management. UC after P/OL appears feasible and acceptable, meaning its systematic practice can be scaled up to prevent obstetric fistula and other sequelae of P/OL in low-resource settings. However, SBAs need protocols, in-service training, and consistent supplies, especially in Africa and public facilities.